Tickle your tenses / Dayang Zarinah Awang Bohari ... [et al.] - Awang Bohari, Dayang Zarinah; Chin, Ch'ng Looi; Ibrahim, Sueb; Abang Madaud, Abang Fhaeidzhyall (Universiti Teknologi MARA Shah Alam, 2018)
Learning tenses is an uphill task for ESL (English as a Second Language) learners, especially children. One of the reasons is that grammatical structures in English are inherently different from those of the mother tongue. More often than not learners find it difficult to comprehend and apply the rules accurately for effective communication. Hence, they become frustrated and give up trying to learn the language. The main purpose of TYT is to address the said problems faced by these learners besides providing a fun, exciting and interactive environment to reinforce the rules of tenses learnt. Presently, English language games tend to focus on parts of speech and vocabulary learning but not many emphasise on tenses. TYT fills in the gap to reinforce the learning of tenses and its application in different everyday contexts. Children can learn with their peers while playing in an enjoyable setting which will promote better retention of their tenses knowledge. TYT is also useful for language educators as an alternative teaching tool to drill the rules of tenses which otherwise would be too monotonous and dry for students in the classroom